Influence of Resting Blood Pressure on Functional Fitness: An Experimental Study Comparing Hypertensive and Normotensive Older Women - Diogo Cardozo (Asociación Española de Ciencias del Deporte, 2021)
Introduction:  Hypertensive older adults have reduced blood flow and oxygen supply as compared to normotensive individuals. These negative adaptations can negatively impact muscle function. Although the vascular consequences of systemic arterial hypertension (SAH) have been extensively discussed, the literature on functional fitness (FF) in hypertensive older persons is limited. The objective of the present study was to investigate the influence of resting blood pressure (BP) on functional fitness in hypertensive as compared to normotensive older women. Methods: A total of 48 older women were included according to their resting BP: 24 from the normal BP group (GNBP) and 24 from the high BP group (GHBP). Anthropometric measurements and FF (30s Chair Stand, Arm Curl, Chair Sit and Reach and 8-Foot Up-and-Go) were investigated. Results: The comparison between groups revealed that the GNBP had a higher number of repetitions in the 30s chair stand test (p=0.007, d=0.618) as compared to the GHPB. Conclusion: Hypertensive older women have lower values of lower limb muscle strength compared to normotensive older women. Therefore, functional tests that measure muscle strength of lower limbs may be adapted for this population.